Quantitative Skeletal Muscle Imaging Using 3D MR Fingerprinting With Water and Fat Separation. Issue 5 (30th September 2020) - Marty, Benjamin; Lopez Kolkovsky, Alfredo L.; Araujo, Ericky C.A.; Reyngoudt, Harmen
Abstract : Background: Quantitative muscle MRI is a robust tool to monitor intramuscular fatty replacement and disease activity in patients with neuromuscular disorders (NMDs). Purpose: To implement a 3D sequence for quantifying simultaneously fat fraction (FF) and water T1 (T1, H2O ) in the skeletal muscle, evaluate regular undersampling in the partition‐encoding direction, and compare it to a recently proposed 2D MR fingerprinting sequence with water and fat separation (MRF T1 ‐FF). Study Type: Prospective. Phantom/Subjects: Seventeen‐vial phantom at different FF and T1, H2O, 11 healthy volunteers, and 6 subjects with different NMDs. Field Strength/Sequence: 3T/3D MRF T1 ‐FF, 2D MRF T1 ‐FF, STEAM MRS ASSESSMENT: FF and T1, H2O measured with the 2D and 3D sequences were compared in the phantom and in vivo at different undersampling factors (US). Data were acquired in healthy subjects before and after plantar dorsiflexions and at rest in patients. Statistical Tests: Linear correlations, Bland–Altman analysis, two‐way repeated measures analysis of variance (ANOVA), Student's t‐ test. Results: Up to a US factor of 3, the undersampled acquisitions were in good agreement with the fully sampled sequence (R 2 ≥ 0.98, T1, H2O bias ≤10 msec, FF bias ≤4 × 10 –4 ) both in phantom and in vivo. The 2D and 3D MRF T1 ‐FF sequences provided comparable T1, H2O and FF values (R 2 ≥ 0.95, absolute T1, H2O bias ≤35 msec, and absolute FF bias ≤0.003). The plantar dorsiflexion induced a significant increase of T1, H2O in the tibialis anterior and extensor digitorum (relative increase of +10.8 ± 1.7% and + 7.7 ± 1.4%, respectively, P < 0.05), that was accompanied by a significant reduction of FF in the tibialis anterior (relative decrease of –16.3 ± 4.0%, P < 0.05). Some subjects with NMDs presented increased and heterogeneous T1, H2O and FF values throughout the leg. Data Conclusion: Quantitative 3D T1, H2O and FF maps covering the entire leg were obtained within acquisition times compatible with clinical research (4 minutes 20 seconds) and a 1 × 1 × 5 mm 3 spatial resolution. Level of Evidence: 2 Technical Efficacy: Stage 2